Combination of Oncolytic Measles Virus Armed With BNiP3, a Pro-apoptotic Gene and Paclitaxel Induces Breast Cancer Cell Death - Lal, Geetanjali; Rajala, Maitreyi S. (Frontiers in Oncology, 2019)
Breast cancer is one of the major causes of cancer related mortality in women worldwide. Limitations of conventional anti-cancer therapies such as severe systemic side effects, narrow therapeutic index, non-specificity and non-availability of drugs for all types of cancers has resulted in the development of various novel and targeted approaches. The use of viruses as oncolytic agents has gained momentum for the development of an efficient therapeutic platform. In this study, we have developed recombinant measles virus armed with BNiP3, a pro-apoptotic gene of human origin, as an oncolytic agent and have demonstrated its ability to induce apoptosis in breast cancer cells in vitro. Studies have demonstrated the potential of using oncolytic viruses in combination with conventional therapies as an efficient anti-cancer regimen. We also have explored the synergistic potential of this virus in combination with paclitaxel, and a hydrazone derivative, H2 compound as an anti-cancer agent. MCF-7 and MDA-MB-231, human breast cancer cell lines were used for in vitro studies to evaluate toxic effects of armed virus, rMV-BNiP3 both as a standalone therapy and in combination with paclitaxel or H2 compound, a hydrazone derivative. Generation of armed virus was confirmed by detecting the viral transcript and protein expression, while its oncolytic potential by cell viability assays. Induction of apoptosis was demonstrated by fluorescence based caspase 3 activity and flow cytometry based Annexin V/PI staining. In the current study we have demonstrated the successful generation of an oncolytic measles virus armed with BNiP3 (rMV-BNiP3) and the induction of toxic effects in rMV-BNiP3 infected cells with a curious bias towards MDA-MB-231 cells as compared to MCF-7. Infection of breast cancer cells with rMV-BNiP3 caused induction of cell death, but the combination of rMV-BNiP3 with sub-lethal doses of both paclitaxel and H2 lowered the overall viability of cancer cells. As triple negative breast tumors are highly aggressive and resistant subtype of breast cancer with poor prognosis, comparative sensitivity of MDA-MB-231 cells towards this virus may potentially be used to develop a targeted therapy against triple negative breast cancer.